2014
DOI: 10.4028/www.scientific.net/amm.575.766
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of Laser Polishing Process

Abstract: Laser polishing is a finishing process based on melting material, with the objective of improving surface topography. Some operating parameters must be taken into consideration, such as laser power, feed rate, offset, and overlapping. Moreover, because of its dependence on the primary process, the initial topography has also an impact on the final result. This study describes a quadratic model, conceived to optimize final topography according to the primary process and laser polishing. Based on an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In terms of CW-LP and zigzag strategy, the term "overlap" concerns the distance between parallel laser lines, while, in LµP, where pulsed lasers are used, the overlap value is also calculated along the scanning direction and, therefore, depends on the scanning speed, beam diameter, pulse rate frequency, and pulse duration [20,21]. Rosa et al showed that overlap is a vital parameter in the case of the optimization of the CW-LP process [22]. Bhaduri et al investigated the LP of 3D printed parts that were made of 316L steel [21].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of CW-LP and zigzag strategy, the term "overlap" concerns the distance between parallel laser lines, while, in LµP, where pulsed lasers are used, the overlap value is also calculated along the scanning direction and, therefore, depends on the scanning speed, beam diameter, pulse rate frequency, and pulse duration [20,21]. Rosa et al showed that overlap is a vital parameter in the case of the optimization of the CW-LP process [22]. Bhaduri et al investigated the LP of 3D printed parts that were made of 316L steel [21].…”
Section: Introductionmentioning
confidence: 99%
“…They identified the input thermal energy as the key parameter affecting melt pool convection and controlling the surface quality. Rosa et al [52] proposed a quadratic model taking into account the initial surface topography and polishing process parameters. Using the model, they predicted the polished surface quality and also experimentally determined the optimal parameters for polishing.…”
Section: Introductionmentioning
confidence: 99%